An Exploring for Social Innovation Towards Social Enterprise Growth - Photchanachan, Sarana; Thechatakeng , Pusanisa; Uppapong , Kullaya (Business Administration and Management Journal Review, 2023)
The term of social innovation has been increasingly recognized in recent years. However, there is still lack of consensus definition and practice. The objective was to explore the social innovation that can be led to social enterprise growth in Thailand. The method was multiple cases study, which was qualitative research. Purposive sampling and the extreme cases were used to select 10 social enterprise owners and in-depth interview 10 social entrepreneurs. A data was analyzed by using grounded analysis. To get validity and reliability information, the interview to the expert of social entrepreneurship who has experienced in many years, this will give a reliable on the information. The results indicated that social innovation was improving the quality of community life by developing social services and new products, looking for solutions to create social change, developing new training techniques to increase the innovative capacity of the community, new technologies to solve problems and find solution to social need, creating novel ideas, ways to increase social interaction, looking for opportunities, and useful for community without any expectation of any financial benefit. Thus, each of social innovation is creating the impact to the society and community area that each of key informants lived in.